HUBUNGAN ANTARA PERTUMBUHAN INDUSTRI, PERDAGANGAN INTERNASIONAL TERHADAP KONSENTRASI INDUSTRI DAN PERTUMBUHAN EKONOMI DI JAWA TIMUR - Bambang Heru Santosa (Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
Objectives of the study is to analyze causal relationships among five variables. The first three, development of industry influenced to the development of economy (economic growth), to concentration of industry, and to welfare. Second, concentration of industry pushed the economic growth. The third three, the international trade influenced to concentration of industry, to economic growth, and to welfare. Finally, the impact of economic growth to welfare. This analysis using structural equation modeling (SEM) and found that five of eight relationships were significant and the rest were insignificant. First, development of industry negatively influenced concentration of industry. Second, international trade pushed concentration of industry. Third, concentration of industry also pushed economic growth. Fourth, international trade positively influenced economic growth. Finally, the economic growth positively influenced welfare. The development of industry was insignificant influence to the economic growth, and positively influenced to welfare. It is negativite relation was caused by dispersion of the location of industry, so resulted low economies of scale. International trade was negatively influenced welfare. Policy implication obtained from the whole analyses, especially for the East Java Provincial Government. In order to improve performance of the economy, it is suggested employing the Integrated Territory-provincial Planning based on comparative advantage among regions.